Factors Related to The Activity Of Posyandu Cadres in The Immunization Program of Sudirejo Village I - Siagian, Laili; Hasibuan, Rapotan (Universitas Nahdlatul Ulama Surabaya, 2024)
In posyandu, the role of cadres is to be able to show their figure and be active in one of the health programs, namely immunization. Posyandu Sudirejo I village is under the coordination of puskesmas Simpang Limun with 11 (42.31%) active posyandu. This study aims to determine the factors associated with the activeness of posyandu cadres in the immunization program in Sudirejo I village, Medan City. The method in the study used quantitative methods with a cross sectional research design. A total of 55 cadres were used as samples using univariate and bivariate analysis using the chi-square test (p<α0.05). The results showed that active respondents were 29 (52.7%), while inactive respondents were 26 (47.3%). There are results of several research variables, namely knowledge (p 0.002 <α 0.05), motivation (p 0.002 <α 0.05), infrastructure (p 0.022 <α 0.05), interpersonal relationships (p 0.875>α 0.05) and incentives (p 0.324>α 0.05) in the posyandu immunization program. The conclusion is that, knowledge, motivation and infrastructure are related to the activeness of posyandu cadres while interpersonal relationships and incentives are not related to the activeness of posyandu cadres in the immunization program in Sudirejo I village, Medan City.